Study of carotid intimal thickness in ischemic stroke and coronary artery disease - Dharmendra Uraiya; VK Verma; Anoop Kumar; N. Tripathi; RR Singh (International Journal of Medical Research and Review, 2016)
Introduction: Intima medial thickness of common carotid arteries can be used to measure generalized atherosclerosis and also surrogate marker of coronary artery disease and ischemic stroke. It is extensively used examine the carotid IMT and to evaluate the regression of atherosclerosis lesion in interventional studies.Material and methods: It was a cross sectional study conducted in the department of Medicine of a tertiary care centre, Indore, India. Carotid ultrasonography examinations were performed with the use of shimad Zu (SDU 2200) & Toshiba just vision-400 sonography machine equipped with a 7.5 to 10 MHz linear-array transducer. With the subject in the supine position and the neck in slight hyperextension the common carotid artery, carotid bulb, and the extra-cranial part of internal carotid artery was identified of both side and IMT was measured as the distance between the luminal Intimal interface and the medial adventitial interface.Results: P < .001 which is highly significant i.e. increased IMT is strong risk factor for Ischemic stroke and CAD in all the age groups. P < .001 which is highly significant i.e. increased IMT is strong risk factor for both ischemic stroke and Coronary artery disease. When carotid intimal thickness between patients of ischemic heart disease and coronary artery disease is compared, we observed a P value > .05, which is not significant, i.e. there is no much difference of IMT in ischemic Stroke and Coronary artery disease.Conclusion: Parkinson’s disease and Parkinson plus syndrome is a group of sporadic, neurodegenerative diseases of the central nervous system. There are only a few reports about the frequency of neuropsychiatric symptoms in patients with Parkinson disease from India and no such Indian report in patients with Parkinson plus syndrome